PENGARUH LABEL HALAL, KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK MINUMAN SARI APEL DI DESA ANDONOSARI - Alifiyatul Fitriyah; Noor Shodiq Askandar; Afifuddin Afifuddin (El-Aswaq, 2021)
This study aims to determine the effect of partial and simultaneous halal label, productquality and price on consumer purchasing decisions on apple cider beverage productsin Andonosari village. This research is a quantitative research. The method used to testthe hypothesis is to use an instrument test, normality test, classical assumption test,multiple linear regression analysis and hypothesis testing with simultaneous test (Ftest), coefficient of determination (R2) and partial test (t test). The sample in this studywas 52 respondents with the provisions that each respondent is a consumer of AppleSari beverage products who reside in the Andonosari Village area and consumers whoknow and have consumed Apple Sari beverage products. The data used is primary dataobtained directly through consumer questionnaires on apple cider beverage products inAndonosari village. The results showed that the halal label, product quality and pricehad an effect either partially or simultaneously on purchasing decisions on apple ciderdrink products in Andonosari village. The results of the research on the hypothesis,show that the halal label has a positive and significant effect on purchasing decisions,product quality has a positive and significant effect on purchasing decisions, and pricehas a positive and significant effect on purchasing decisions.